2015
DOI: 10.3390/rs71014227
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of EnMAP and Sentinel-2 Data for Detecting Drought Stress Phenomena in Deciduous Forest Communities

Abstract: Given the importance of forest ecosystems, the availability of reliable, spatially explicit information about the site-specific climate sensitivity of tree species is essential for implementing suitable adaptation strategies. In this study, airborne hyperspectral data were used to assess the response of deciduous species (dominated by European beech and Sessile and Pedunculate oak) to water stress during a summery dry spell. After masking canopy gaps, shaded crown areas and non-deciduous species, potentially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 93 publications
0
33
0
Order By: Relevance
“…However, most other studies [24][25][26][27][28][29]31] on initial results with Sentinel-2A MSI did not specifically mention this as an observation or a problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most other studies [24][25][26][27][28][29]31] on initial results with Sentinel-2A MSI did not specifically mention this as an observation or a problem.…”
Section: Discussionmentioning
confidence: 99%
“…Now that actual Sentinel-2A MSI data are available, several studies have been undertaken to confirm prior findings. The majority comprises vegetation related studies, such as crop and tree species classification [24]; forest crowns [25,26]; chlorophyll and nitrogen [27] and biomass [28], as well as applications involving water, such as mapping water bodies [29]; water quality [30] and lake shore habitats [31].…”
Section: Introductionmentioning
confidence: 99%
“…Water parameters, such as short-and long-term water stresses on deciduous forest communities, could also be retrieved [96]. Both simulated EnMAP and S2 data allowed a good estimation of drought indicators such as Moisture Stress Index (MSI), Chlorophyll Index (CI) and Simple Ratio (SR).…”
Section: Preliminary Analysis Of the Literature Databasementioning
confidence: 99%
“…This activity resulted in several experiments based on simulated S2 datasets [5][6][7][8][9][10][11][12][13][14][15]. These studies reported a high potential of S2 in various fields of application.…”
Section: Introductionmentioning
confidence: 99%